Religion, Labour, and National Questions: The General Election of 1924 in Belfast and Lanarkshire. Issue 3 (December 2019) - Walker, Graham; Greer, James
Abstract : Through a comparative analysis of the 1924 Westminster constituency elections in West Belfast and Motherwell, this article examines how Labour campaigns sought to negotiate religious divisions and questions of national allegiance. The striking commonalities in both campaigns and constituencies highlight the precarious coalitions that Belfast and Scottish Labour sought to maintain at this time, and how religious and national identities could provide both resources and obstacles for varieties of Labour politics. This comparative analysis also advances understanding of religious and political bonds and divergences between Scotland and Northern Ireland.